2017
DOI: 10.3168/jds.2016-12284
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the capillary electrophoresis method for measurement of immunoglobulin concentration in ewe colostrum

Abstract: Capillary electrophoresis (CE) is a technique routinely used in clinical laboratories that allows the separation and quantification of blood serum proteins in a rapid, precise, accurate, and inexpensive manner. Recently, CE has been proposed to separate and measure colostral proteins, but an evaluation of the agreement between CE and radial immunodiffusion (RID) method, currently used to quantify IgG in colostrum, is still lacking. The purpose of this study was to test the ability of a CE instrument, normally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
(21 reference statements)
1
13
0
Order By: Relevance
“…Appropriate preventative measures rely on the accurate and timely determination of the passive immune status in neonatal lambs and, therefore, they are important in the reduction of morbidity and mortality rates (Gokce and Erdogan 2009;Gokce et al 2013;Lopreiato et al 2017;Voigt et al 2019). This study has demonstrated the accuracy of SGGTA, a test that can be adapted to the field as almost all veterinarians have a blood chemistry analyser for determining the passive immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate preventative measures rely on the accurate and timely determination of the passive immune status in neonatal lambs and, therefore, they are important in the reduction of morbidity and mortality rates (Gokce and Erdogan 2009;Gokce et al 2013;Lopreiato et al 2017;Voigt et al 2019). This study has demonstrated the accuracy of SGGTA, a test that can be adapted to the field as almost all veterinarians have a blood chemistry analyser for determining the passive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the first day after birth is the most critical time for lambs, since the failure of passive transfer (FPT) occurs at this time. FPT is a secondary immunodeficiency condition that predisposes newborn ruminants to the development of common neonatal diseases and adversely influences their performance later in life (Massimini et al 2006;Gokce et al 2013;Gokce et al 2014;Lopreiato et al 2017). Failure of passive transfer (FPT) and the resulting hypogammaglobulinemia have also been linked to an increased risk of neonatal illnesses and deaths (Britti et al 2005).…”
mentioning
confidence: 99%
“…Immunoglobulin G (IgG) measurement has traditionally been required to establish the absence of colostrum in the domestic consumer milk supply [14]. Several techniques, such as ELISA [15], capillary electrophoresis [16] or more traditional methods like Brix refractometry [17] and the use of colostrometers [18] have been employed for IgG detection. The most widely used method for such analysis is radial immunodiffusion [10].…”
Section: Introductionmentioning
confidence: 99%
“…; Lopreiato et al . ) or traditional methods such as Brix refractometer (Quigley et al . ) and colostrometer (Bartier et al .…”
Section: Introductionmentioning
confidence: 99%
“…To date, several methods have been developed to determine colostral IgG concentration. These methods include radial immunodiffusion (RID) (Mancini et al 1965), ELISA (Gelsinger et al 2015), electrophoresis (Ceniti et al 2016;Lopreiato et al 2017) or traditional methods such as Brix refractometer (Quigley et al 2013) and colostrometer (Bartier et al 2015). This latter method, which reveals the chemical and physical properties, measures colostrum density allowing for the direct assessment of immunoglobulin concentration.…”
Section: Introductionmentioning
confidence: 99%